Yöneticilerin okullarda değişim yönetimini gerçekleştirebilme yeterlilikleri - Yılmaz, Seven (My University, 2004)
THE MANAGERS' SUFFICIENCY OF REALIZING CHANGE MANAGEMENT AT SCHOOLS The National Education system must be put into a form according to the country and economic necessities. At the same time this system must have a dynamic structure. The ability of solving problems via education should be developed and solutions for problems should be found immediately. So information alternatives will be taken off being just alternatives and this makes us Information Society. At schools there will also be change desires to provide adaptation for changing conditions in the future. So the topic How to Manage the Change at Schools is a topic that must be researched and put into a form. The strategies and tactics regarding to the way that the changes will be supplied must be obtained according to modern approaches. The change plans, the way of managing the change, how it will be realized, and how it will be controlled must be determined previously. In Turkey that is at the process of European Community candidacy: Public sector must be re-formed, but it is not enough by itself. The change in Turkey means to realize -being pieces of a whole- economic, democratic, administrative, political, and legal changes. The meaning of reform in the education according to a different mind is to change the education system from head to foot (entirely). In this study, we will talk about changing applications that realized at schools, so the concept organizational change will be discussed besides. This study consists of six chapters. The first chapter is introduction. The second chapter contains regarding publications. The third chapter describes the method of research. The fourth chapter includes the findings that obtained from the study. The fifth chapter is the conclusion of the research, and finally the sixth chapter contains discussions. Some important conclusions of the research are: In the primary education schools the change is sometimes being realized because of technologic age and Total Quality Management applications. Mostly the changes which Ministry of Education instructions force are applied. According to opinions of the teachers that joined our poll, the managers of the schools, sometimes realize most attributes of change leadership. HAZİRAN 2004 Seven YILMAZ

YÖNETİCİLERİN OKULLARDA DEĞİŞİM YÖNETİMİNİ GERÇEKLEŞTİREBİLME YETERLİLİKLERİ Milli Eğitim sisteminin ülkenin ve ekonominin ihtiyaçlarına göre yeniden biçimlenmesi gerekmektedir. Aynı zamanda bu sistemin dinamik bir yapıya kavuşturulması gerekmektedir. Eğitim yolu ile sorunlarımızı çözme kabiliyetimizi geliştirerek sorunlara çözüm bularak ve bilgi alternatiflerini, alternatif olmaktan çıkararak Bilgi Toplumu haline gelmemiz mümkün olacaktır. Okullarda gelecekte de değişen koşullara uyum sağlamak için benzer değişim istekleri olacaktır. Bu nedenle değişimin okullarda nasıl yönetileceği araştırılması ve biçimlendirilmesi gereken bir konudur. Çağdaş yaklaşımlara göre değişmenin nasıl yapılacağına ilişkin stratejilerin ve taktiklerin belirlenmesi gerekir; değişme planları değişmenin nasıl yönetileceği ,nasıl gerçekleştirileceği nasıl kontrol edileceği , önceden belirlenmelidir. Avrupa Birliği'ne üye adaylık sürecindeki Türkiye' de , Kamu kesiminin yeniden yapılanması, gereklidir, ancak elbette tek başına yeterli değildir. Türkiye'de değişim, bir bütünün parçaları olan ekonomik ,demokratik, idari, siyasi ve hukuki alanlardaki değişimlerin başarılması demektir. Bir başka anlayışa göre de eğitimde reformun anlamı eğitim sistemini en üstten en alta kadar değiştirmektir. Bu çalışmada ,okullarda gerçekleşen değişim uygulamalarından bahsedileceği için örgütsel değişim kavramı üzerinde durulacaktır. Bu çerçeve içinde değişim yönetimi aşamaları ile ilgili bilgi verilecek ve değişim yönetimi aşamalarından ,uygulamalarından bahsedilecektir. Bu çalışma altı bölümden oluşmaktadır. yayınlardır. Üçüncü bölüm araştırmanın yöntemi, dördüncü bölüm elde edilen bulgulardan oluşmaktadır. beşinci bölümde ise araştırmanın sonuçları ve altıncı bölümde tartışmalar ele alınmıştır. Araştırmanın bazı önemli sonuçları şunlardır: İlköğretim okullarında teknolojik eskime nedeni ile ve Toplam Kalite Yönetimi uygulamaları için bazen değişim gerçekleştiriliyorken çoğu zaman Milli Eğitim Bakanlığı'nın yönetmelikleri gereği yapılması zorunlu olan değişiklikler uygulanmakta.Okul yöneticileri de değişim liderliği vasıflarının bir çoğunu anketimize katılan öğretmen görüşlerine göre bazen yerine getirmektedir. HAZİRAN 2004 Seven YILMAZ
Keywords: Eğitim; Okul organizasyonu ve yönetimi